Inclusion of sex chromosomes in noninvasive prenatal testing in Asia, Australia, Europe and the USA: A survey study. (7th February 2023) - Steffensen, Ellen Hollands; Skakkebæk, Anne; Gadsbøll, Kasper; Petersen, Olav Bjørn; Westover, Thomas; Strange, Heather; ,; Vogel, Ida
Abstract: Objective: To examine the extent to which sex chromosomes are included in current noninvasive prenatal testing (NIPT) and the reporting practices with respect to fetal chromosomal sex and sex chromosome aberrations (SCAs), in addition to an update on the general implementation of NIPT. Method: A questionnaire addressing the research objectives was distributed by email to fetal medicine and clinical genetics experts in Asia, Australia, Europe and the USA. Results: Guidelines on NIPT are available in the majority of the included countries. Not all existing guidelines address reporting of fetal chromosomal sex and SCAs. In most settings, NIPT frequently includes sex chromosomes (five Australian states, China, Hong Kong, Israel, Singapore, Thailand, USA and 23 of 31 European countries). This occurs most often by default or when parents wish to know fetal sex. In most settings, a potential SCA is reported by stating the risk hereof as "low" or "high" and/or by naming the SCA. Less than 50% of all pregnant women receive NIPT according to respondents from three Australian states, China, Israel, Singapore, Thailand and 24 of 31 European countries. However, this percentage, the genomic coverage of NIPT and its application as primary or secondary screening vary by setting. Conclusion: In most of the studied countries/states, NIPT commonly includes sex chromosomes. The reporting practices concerning fetal chromosomal sex and SCAs are diverse and most commonly not addressed by guidelines. In general, NIPT is variably implemented across countries/states. Key points: What is already known about this topic? Noninvasive prenatal testing (NIPT) has been widely adopted in many countries. NIPT allows screening for sex chromosomes including sex chromosome aberrations (SCAs); however, positive predictive values are lower than for trisomies 13, 18 and 21. What does this study add? In 30 out of 38 countries surveyed, NIPT commonly includes sex chromosomes, either automatically or based on a parental wish to know fetal sex. Reporting practices concerning fetal chromosomal sex and SCAs based on NIPT are diverse and often not founded in guidelines. In most countries studied, less than 50% of pregnant women receive NIPT; however, this proportion varies substantially between settings.